Antibacterial, Antioxidant, and Cytotoxic Properties of Eclipta prostrata Extracts - Wongkattiya, Nalin; Sanguansermsri, Phanchana; Akawatchai, Chareeporn; Fraser, Ian; Sanguansermsri, Donruedee (HAYATI Journal of Biosciences, 2024)
Eclipta prostrata is traditionally used in Asian medicine to treat skin diseases. Given the side effects and bacterial resistance of conventional treatments, especially in aging populations, alternative therapies are needed. This study assesses the antibacterial, antioxidant, and cytotoxic properties of E. prostrata extracts, focusing on optimizing extraction and fractionation methods for better efficacy. Dried whole plants were extracted with ethanol. Antibacterial activity was tested against Staphylococcus aureus, MRSA, S. epidermidis, and Pseudomonas aeruginosa using broth microdilution to determine minimum inhibitory concentrations (MIC). Antioxidant activity was assessed using a DPPH radical scavenging assay, and cytotoxicity was tested in Vero cells using an MTT assay. The MIC values for crude ethanol extracts ranged from 1.56 to 3.12 mg/ml, and from 0.78 to 1.56 mg/ml for fractionated compounds, indicating increased antibacterial efficacy in fractionated compounds. Antioxidant assays showed an IC50 of 0.666 mg/ml for crude extracts and 0.174 mg/ml for fractionated compounds, indicating higher antioxidant activity. Total phenolic content was 23.25±2.03 mg GAE/g for crude extracts and 95.56±1.09 mg GAE/g for fractionated compounds. Cytotoxicity assays showed IC50 values of 0.10±0.02 mg/ml for crude extracts and 0.06±0.01 mg/ml for fractionated compounds. This study advances extraction and fractionation methods, yielding extracts with significantly increased antibacterial and antioxidant properties. E. prostrata extracts, particularly fractionated compounds, show promising therapeutic potential, though high cytotoxicity in some fractions requires further investigation. These findings support the potential of E. prostrata in modern pharmaceutical formulations for treating skin conditions, especially those associated with aging.